Unlocking the Power of Tuberculinum: Effective Nosode Utilization in Homeopathy – A Case Report (Homoeopathy for All, 2025)
Tuberculinum is a combination of Psora and Syphilis i.e. Tubercular miasm or Pseudo psora. The main feeling in this miasm is that of being shut in, cramped, suffocated and to get out from such a situation. The tubercular miasm seems to demand a need for rapid change as a condition of survival. The sensation of suffocation especially when struck in a particular place and the need for hectic, intense activity are the two aspects of tubercular miasm. As Tuberculinum is a nosode, the basic theme of nosode is desperation and this desperation is expressed in every sphere of life of a person who requires them. It shows psoric manifestations like irritability, restlessness and syphilitic manifestations like destructiveness, wildness and cruelty.
Keywords: Nosodes; Multipolychrest; Culture of bacilli; Phthisis; Intellectual types; Hyperactive; Tuberculosis; Plica polonica